FORMULATION AND EVALUATION OF HERBAL FLOATING TABLET OF PIPERINE FOR CONSTIPATION - SHARMA, PRIYANKA; KUMAR, RAJESH; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
Objective: To formulate and evaluate a herbal floating tablet of piperine intended for the treatment of constipation, with an emphasis on understanding how different polymer. Methods: Floating tablets were prepared using direct compression and designed via a three-factor, three-level Box–Behnken experimental design. The independent variables were the amounts of HPMC K4M (A), HPMC K100M (B), and xanthan gum (C). Tablets were assessed for physicochemical properties (thickness, weight variation, friability, hardness), buoyancy parameters (floating lag time—FLT), swelling index (SI), and time to 90% drug release (T90%). Data was analyzed to determine the effect of polymer blends on tablet performance. Results: The floating tablets varied from 81.12±0.63 to 119.7±0.567 sec, rising with larger polymer concentrations and longer hydration. HPMC K100M had the greatest FLT, followed by xanthan gum and HPMC K4M due to hydrophilicity and molecular weight. The swelling index varied from 61.9±0.624% to 99.95±0.226%. HPMC K100M and xanthan gum swelled more. Time to 90% drug release (T90%) varied from 7.0±0.55 to 10.33±0.289 h, with increased polymer viscosity and concentration delaying release. HPMC-xanthan gum polymers caused synergistic swelling and regulated drug release with zero-order kinetics. Conclusion: The floating, swelling, and drug release kinetics of floating tablets depend on polymer selection and mixing. HPMC K100M and xanthan gum alone or in combination provide tablet matrices with better integrity, stomach retention, and drug release. This allows controlled-release oral formulations with enhanced constipation treatment.